Usability Analysis of Sapa Warga Application Using Usability Testing Method and System Usability Scale (SUS) - Muhammad Alfin Arroyan; Rio Guntur Utomo; Kusuma Adi Achmad (LPPM STIKOM Tunas Bangsa, 2024)
Sapawarga is software used to fulfill the needs of citizens in a variety of services, ranging from public information, letter submission, to public complaints. There are some negative comments about the application on the Google app store. This suggests there are quality issues in the Sapawarga software. By applying usability tests, namely the System Usability Scale (SUS), and SPSS for data analysis, this study aimed to ascertain user satisfaction features with the SapaWarga application. The study collected primary Data from distributed questionnaires to 400 respondents from Bandung City residents. It has been determined that the application achieved a total score of 52.92, which is classified as OK. However, the grade scales and acceptability ranges were relatively low, indicating that there are still many improvements needed to achieve maximum user satisfaction. In the paper, the researchers provided recommendations for enhancing the usability of the Sapawarga application in West Java